The Princippal's Prophetic Leadership in Improving Teacherâ€™s Performance - Nafi'a, Ilman; Gumiandari, Septi (JIEM (Journal of Islamic Education Management), 2022)
The performance of the principal can be a role modeling for the performance of the teachers. If an educational institution is managed with the prophetic leadership ability of the principal, the managerial system will be able to foster responsibility that comes from the hearts and internal motivations of teachers. This study aims to describe the Prophetic Leadership of The Principal in Improving Teacher Performance. This research uses a literature reviews approach. In searching for articles, a google scholar application is used with the keywords "Prophetic Leadership,â€ â€œPrincipal,â€ and â€œTeacher Performance.â€ Article searches are time-limited i.e. from 2016 to 2021. From the search results, 20 articles were searched based on thematic criteria, up to only 12 articles were used in this study. The results showed that the leadership of the principal in an Islamic educational institution went well and ideally according to the concept of the Qur'an and Hadith when each leader was able to practice prophetic values (shiddiq, amanah, tabligh, fathonah) with full responsibility in carrying out the wheels of education. The implementation of prophetic values in leading by a principal leader will affect the improvement of teacher performance as an effort to answer the hopes, wants, and needs of the community. In other words, there is a significant relationship between the principal's prophetic leadership and teacher performance